2022
DOI: 10.1186/s13017-022-00425-z
|View full text |Cite
|
Sign up to set email alerts
|

The weekend effect on the provision of Emergency Surgery before and during the COVID-19 pandemic: case–control analysis of a retrospective multicentre database

Abstract: Introduction The concept of “weekend effect”, that is, substandard healthcare during weekends, has never been fully demonstrated, and the different outcomes of emergency surgical patients admitted during weekends may be due to different conditions at admission and/or different therapeutic approaches. Aim of this international audit was to identify any change of pattern of emergency surgical admissions and treatments during weekends. Furthermore, we aimed at investigating the impact of the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Early postoperative bleeding is linked to longer hospitalization, major complications (such as sepsis and organ failure), reoperation and mortality [20][21][22][23]. Therefore, there is a need for preventive strategies in bariatric surgery due to the severe consequences of early postoperative.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative bleeding is linked to longer hospitalization, major complications (such as sepsis and organ failure), reoperation and mortality [20][21][22][23]. Therefore, there is a need for preventive strategies in bariatric surgery due to the severe consequences of early postoperative.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentre study during the first wave of the pandemic reported a one-third reduction of emergency surgical admissions both during workdays and weekends. 9 Whereas, a Scottish study reported a significant increase in severe appendicitis resulting in greater proportion of emergency surgery and operative time. 10 Additionally, a regional New Zealand study reported patients with appendicitis were 15.1 years younger their counterparts (21.5 vs. 36.6, p<0.01), had a longer onset of symptoms During the first wave, Bankstown-Lidcombe hospital was a relatively spared centre like many other major Australian hospitals as resources were re-allocated towards major COVID-19 hospitals for expectant management of cases.…”
Section: Discussionmentioning
confidence: 99%
“…16 The term 'weekend effect' has been described as a suspected epidemiological effect causing substandard care during weekends due to higher workload and lower capacities of the healthcare system compared with workdays. 39 A 'weekend effect' has been described for other medical areas such as provision of emergency surgery or appropriate antibiotic prescription. [39][40][41][42] Higher reporting of COVID-19 case counts from Tuesday to Friday and day of week fluctuations have also been reported by regional studies and were attributed to temporal changes in laboratory testing and use of healthcare facilities as well as reporting delays.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…39 A 'weekend effect' has been described for other medical areas such as provision of emergency surgery or appropriate antibiotic prescription. [39][40][41][42] Higher reporting of COVID-19 case counts from Tuesday to Friday and day of week fluctuations have also been reported by regional studies and were attributed to temporal changes in laboratory testing and use of healthcare facilities as well as reporting delays. 43 44 Thus, for frequently repeated decision processes like ad hoc travel restrictions, it seems to be reasonable to use case counts reported in the middle of the week for ad hoc political decision-making to avoid underestimation of case counts.…”
Section: Strengths and Limitationsmentioning
confidence: 99%